Hipertensi Gestasional : Literature Review - Ardia Syifa Wijaya (Fakultas Kedokteran Universitas Lampung, 2024)
Gestational Hypertension: Literature Review ABSTRACT Hypertension is blood pressure over 140/ 90 mmHg. Hypertension is one of the global problems that plague the world. Gestational hypertension is one of the causes of maternal and infant morbidity and mortality worldwide. Gestational hypertension is detrimental to the mother and fetus and risks other cardiovascular diseases later in life. This review aims to find out the latest updates related to gestational hypertension. The articles used in this journal are articles obtained from searching the PubMed database, Google Scholar, from 2017 to 2023. The conclusion of this study is that hypertension in pregnancy is one of the leading causes of maternal morbidity and mortality worldwide. Hypertension is associated with pregnancy-related factors, lifestyle and also sociodemographic factors. Pregnant women are expected to maintain a lifestyle and routine control during pregnancy, especially for pregnant women with risk factors for gestational hypertension. Keywords: Hypertension, Gestational